Characteristics of Yogurt with Added Cream using Reconstituted Milk as a Base Ingredient (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2026)
Low fat content weakens gel structure and sensory acceptance, milk cream addition improves yogurtquality. This study aims to analyze the effect of adding cream on the characteristics of yogurt madefrom reconstituted skim milk powder. The treatment consisted of five cream concentrations (0%, 3%,4%, 5%, and 6%) using a completely randomized design (CRD) with three replicates. The parametersobserved included physicochemical properties (pH, aw, viscosity, total acid titratable, syneresis, moisturecontent, and ash content), organoleptic properties (hedonic test and scale), microbiological properties(total lactic acid bacteria and total plate count), and microstructure using polarized and non-polarizedlight microscopes. The result showed that all treatments met the yogurt quality standards based on SNI2981:2009. The addition of milk cream had a significant effect on the physical, chemical, organoleptic,and microstructure characteristics, but had no effect on color and total microbes. Increasing the milkcream concentration produced yogurt with a thicker texture, milder taste, and aroma that was morepreferred by the panelists. Microscopically, the distribution of fat globules was more even and theprotein-fat interaction was more integrated in the gel matrix, enhancing viscosity and reducing syneresis.